P831 Gut mucosal virome alterations and loss of viral-bacterial interactions in ulcerative colitis. (25th January 2019) - Zuo, T; Lu, X; Cheung, C P; Lam, S; Zhang, F; Tang, W; Ching, J; Zhao, R; Chan, P; Sung, J J; Yu, J; Chan, F K; et al.
Abstract: Background: Ulcerative colitis (UC) is associated with gut microbiota dysbiosis. Although alterations in faecal bacteriome and virome have been reported, little is known of the composition and function of the mucosa virome in UC. This is the first study that aims to delineate the configuration and function of mucosal virome in human health and UC. Methods: We performed ultra-deep metagenomic sequencing of virus-like particle preparations and bacterial 16S rRNA sequencing on rectal tissues from 167 Chinese subjects (63 UC, 48 controls from Hong Kong; 20 UC, 20 controls from Beijing). We assessed mucosa virome and bacteriome alterations in UC and correlated alterations with patient meta-data. We also extrapolated mucosa virome enterotypes. Results: In UC, there was an expansion of mucosal viruses, particularly Caudovirales bacteriophages, and a decrease in mucosa viral diversity, richness and evenness compared with healthy controls. Altered mucosa virome correlated with intestinal inflammation. Inter-individual dissimilarity between mucosal viromes was higher in UC than controls. Escherichia phage and Enterobacteria phage were more abundant in the mucosa of UC than controls (FDR adjusted p-value = 1.89e−18 and 4.50e−16, respectively). We clustered the mucosal viral communities of all study subjects into two enterotypes. Enterotype 2 viromes, predominated by UC subjects, displayed a significant loss of viral species. UC patients showed prominent abrogation of viral functions, whereas viral functions associated with bacterial fitness and pathogenicity were markedly enriched in UC mucosa. Intensive Trans-kingdom correlation between mucosa viruses and bacteria were observed in controls but these interactions were significantly lost in UC mucosa Conclusions: UC is characterised by mucosal virobiota dysbiosis with functional distortion. Enrichment of Caudovirales bacteriophages, increased phage/bacteria virulence functions, and loss of viral-bacterial interactions in UC mucosa suggest that dysbiotic mucosal viruses and bacteria may play an important role in UC pathogenesis.